Modeling The Impact Of Animal Farming On Water Quality Of Sg. Serin - Rohene, a/p Srikaran (Universiti Malaysia Sarawak (UNIMAS), 2009)
Animal farming has been cited by the Department of Environment as one of the main sources of water quality degradation in Malaysia. Sg Serin, a tributary of 8atang Samarahan in Sarawak and which has animal farms such as pou ltry and pig farms buill along it, has been showing degrading water quality. The water quality of the river has been assessed and rhe impacts of the farm effluents on the river afe modeled with QUAL2K. The stream water parameters tesred include temperature, pH, dissolved oxygen (~O), 5-day biochemical oxygen demand (BOD,), inorganic (P,,) and organic phosphorus (Po) as well as heavy metals (Zn, Ni and Pb). DO and BOD, levels obtained ranged from 2.24-5.00 mg/L and 1.86-7.99 mg/L respectively while P1Dand Po levels ranged from 0.04-4 .64 mg/L and 0.45-21.11 mg/L respectively. From that range, the lowest DO and the highest BOD5, PIO and Po were all measured in Sg Pam, the tributary thal receives direct discharge from the animal farms. Measured data from the tributaries showed that the tributaries are classified under Class III and IV while Sg Serin itself was under Class II under the Interim National Water Quality Standards for Malaysia. After model calibration and validation, simulation analysis using QUAL2K found lhat untreated animal wastewater would cause the river to be under Class III while treated wastewater would put the river under Class 11. The simulation results conCur with the measured observed da[a which indicates that QUAL2K can be used to successfully predict water quality in Sg Serin